A COMPARATIVE STUDY BETWEEN TRADITIONAL AND DIGITAL STORYTELLING IN IMPROVING LISTENING SKILLS OF ESL LEARNERS - Didi Sudrajat; Kartika Puspandari; Fitria Meisarah (CV. ADIBA AISHA AMIRA, 2024)
Storytelling has long been recognised as an effective method in language learning, but with technological advances, digital storytelling is emerging as an attractive alternative. The research method used was literature. The results show that both methods are effective in improving listening skills, with digital storytelling showing a difference. Digital storytelling is considered more engaging and interactive by learners, while traditional storytelling is considered more personalised and allows direct interaction with the speaker,